A porous tantalum carbide ceramic and its preparation method and application
By using porous tantalum carbide ceramics as filtering materials, the problem of impurities in the preparation of single crystals of silicon carbide is solved, and high purity and high quality silicon carbide single crystal preparation is achieved, and high temperature resistance and strength are provided.
Patent Information
- Application Number
- CN202411240211.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-09-05
AI Technical Summary
The prior art is susceptible to impurities when preparing single crystals of silicon carbide, resulting in defects or impurities in the crystals, affecting their purity and quality.
Porous tantalum carbide ceramics are used as filter material, and porous tantalum carbide ceramics are prepared by mixing tantalum powder and/or tantalum carbide powder with tantalum salt and organic ligand sources in a liquid phase system to form a metal organic frame structure, and decompose or volatilize at high temperature to achieve pore formation, and porous tantalum carbide ceramics with disordered micron-scale pores are prepared.
The porous tantalum carbide ceramic can effectively filter impurities during the growth of single crystals of silicon carbide, improve the purity and quality of the crystal, and have the characteristics of high temperature resistance, high strength and no participation in the reaction, avoiding impurities entering the crystal or forming defects.
Smart Images

Figure CN119100829B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation, and relates to a porous tantalum carbide ceramic and a preparation method and application thereof. Background Art
[0002] As an important functional material, silicon carbide single crystal has broad application prospects in wide bandgap semiconductor devices, high temperature, high frequency, high power electronic devices, light emitting devices and lasers. However, traditional preparation methods such as chemical vapor deposition and flame melting have problems such as high preparation cost, low efficiency and low crystal quality, which are difficult to meet the needs of large-scale production. Therefore, finding an efficient, low-cost and high-quality preparation method has become a hot topic in current research.
[0003] As a new preparation method, physical vapor transport (PVT) has the advantages of high preparation efficiency, low cost and high crystal quality, and has attracted widespread attention. This method is to heat high-purity silicon carbide powder to a high temperature to volatilize it into gas phase components, such as gaseous Si, gaseous Si2C, gaseous SiC2, etc., and then transport the gas phase components to a low-temperature cooling zone to deposit crystals on the seed crystals, and finally generate a silicon carbide single crystal of a certain thickness.
[0004] Although physical vapor transport has many advantages, it also has some challenges and problems, one of which is that it is easily affected by impurities. In the preparation process of silicon carbide single crystals, since the source material is solid and contains impurities or impurities, impurities will be produced during the high-temperature cracking process and will be included in the single crystal growth process, or react with silicon carbide crystals, resulting in defects or impurities in the crystals, which seriously affects the purity and quality of the crystals.
[0005] To this end, the prior art proposes a solution of using porous graphite materials for filtering, placing the porous graphite materials in the area where the gaseous components between high-temperature cracking and low-temperature growth pass through, and using the characteristics of the graphite materials to filter out impurities and impurities in the raw materials, thereby ensuring that the prepared silicon carbide single crystal has higher purity and quality. However, since porous graphite has low strength, is easy to pulverize, and it is easy for it to bring new impurities into the growth environment, more importantly, in a high-temperature environment, graphite will react with the components of the growth environment, which will not only cause the performance of the graphite material to degrade or fail, but also seriously affect the carbon-silicon ratio of the silicon carbide single crystal, resulting in a decrease in preparation efficiency and synthesis quality.
[0006] Therefore, there is still a need to develop a new porous high-temperature resistant material that does not participate in the reaction so as to effectively achieve the filtering effect during the growth of silicon carbide single crystals. Summary of the invention
[0007] In view of the problems existing in the prior art, the purpose of the present invention is to provide a porous tantalum carbide ceramic and its preparation method and application, the preparation method comprising mixing tantalum powder and / or tantalum carbide powder with tantalum salt and organic ligand source in a liquid phase system, forming a solid by rapid cooling, vacuum sintering the obtained solid and then carbonizing it to obtain a porous tantalum carbide ceramic. In the preparation method, the organic ligand source contains an organic ligand, so that it forms a metal organic framework structure with tantalum, adjusts the porosity and distribution, and further decomposes or volatilizes at high temperature to achieve pore formation. The porous silicon carbide ceramic finally prepared has disordered micron-level pores. When used in the preparation of single-crystal silicon carbide by physical vapor deposition, compared with traditional graphite materials, it can allow gaseous substances generated by silicon carbide to pass through, and can withstand high temperatures, and has high strength, does not participate in the reaction, does not produce impurities entering the crystal or forming defects such as carbon encapsulation, and effectively achieves filtering.
[0008] In a first aspect, the present invention provides a method for preparing a porous tantalum carbide ceramic, the preparation method comprising:
[0009] (1) mixing tantalum powder and / or tantalum carbide powder with tantalum salt and an organic ligand source to generate a reactant with a metal organic framework structure to obtain a suspension;
[0010] (2) rapidly cooling the suspension to obtain a solid;
[0011] (3) vacuum sintering the solid to obtain a porous body;
[0012] (4) Carbonizing the porous body to obtain porous tantalum carbide ceramics.
[0013] In the preparation method of the present invention, the metal organic framework structure obtained by mixing the tantalum powder and / or tantalum carbide powder with a tantalum salt and an organic ligand source in a liquid phase system is decomposed and / or volatilized at a high temperature of vacuum sintering to achieve pore formation.
[0014] During the rapid cooling process, bubbles and non-condensable gases will be generated in the suspension. The gas retained in the solidified material will cause defects and unevenness, affecting the material properties. Vacuuming will effectively remove the above gases and reduce defects. In a vacuum environment, the components in the suspension can more easily penetrate and diffuse with each other, which helps to form a more uniform and fine porous structure, and vacuuming can create more space inside the material, thereby increasing the porosity of the material. During rapid cooling, the water in the suspension will be converted into ice and solidify along with other components. In a vacuum environment, solid water can be directly sublimated into water vapor, and while vacuuming, the temperature is rapidly raised to the target temperature to ensure that the remaining water is completely removed. At the same time, organic matter will be extracted along with gaseous water by sublimation or volatilization, stably removing organic matter and further forming a porous structure.
[0015] In the present invention, the purpose of preparing the suspension is to form reactants with a metal-organic framework (MOFs) structure. MOFs are a type of crystalline material with a highly porous structure, which is mainly formed by metal ions and organic ligands connected by self-assembly. In the present invention, tantalum salt provides tantalum metal ions, and organic ligand source provides ligand source, and its addition helps to adjust the valence state and coordination environment of tantalum metal ions and promote the formation of MOFs. In the process of mixing and preparing the suspension, tantalum metal ions directly participate in the formation of MOFs, forming more stable coordination bonds, affecting the stability and catalytic activity of MOFs. Therefore, in the suspension, the molar ratio of metal ions to organic ligands will affect the pore volume and pore distribution of MOFs to a certain extent, and the process flow can be optimized according to specific needs.
[0016] The following are preferred technical solutions of the present invention, but are not intended to be limitations of the technical solutions provided by the present invention. Through the following technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0017] As a preferred technical solution of the present invention, the preparation method comprises: in step (1), tantalum powder and / or tantalum carbide powder is first ball-milled to obtain ball-milled powder, and then the obtained ball-milled powder is mixed with the tantalum salt and the organic ligand source.
[0018] Preferably, the tantalum powder and the tantalum carbide powder are used simultaneously, and the mass proportion of the tantalum carbide powder is controlled to be 50% to 70%, for example, 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68% or 70%, etc.
[0019] The tantalum powder and the tantalum carbide powder are used simultaneously in the present invention, and the two powders with different particle sizes can be interlaced with each other during the ball milling process, which is helpful to form a more complex and uniform pore structure; and the tantalum carbide powder has a high hardness, and will produce more microcracks and defects during the ball milling process, and these defects will be converted into the desired pores during the subsequent heat treatment process.
[0020] Preferably, the ball milling includes liquid phase ball milling, and the liquid medium used in the liquid phase ball milling includes water.
[0021] Preferably, the liquid phase ball milling also uses an oxidant, which includes hydrogen peroxide with a concentration of 25% to 35%, such as 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34% or 35%, etc.
[0022] The present invention adopts liquid phase ball milling, and the liquid medium pure water and hydrogen peroxide can be used as liquid lubricants to take away the heat generated by friction between powder particles and between particles and ball milling medium; help disperse powders and prevent agglomeration, so that liquid phase ball milling is uniform and effective. Hydrogen peroxide, as a strong oxidant, can also help remove organic pollutants and oxidation layers on the surface of powder particles and improve the crystal quality of the material.
[0023] Preferably, the amount of hydrogen peroxide is 5% to 20% of the mass of the liquid medium, for example 5%, 8%, 10%, 12%, 14%, 16%, 18% or 20%, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0024] Preferably, the liquid phase ball milling also uses a strong acid mixture.
[0025] Preferably, the strong acid mixture comprises a mixture of hydrofluoric acid and nitric acid.
[0026] Preferably, the molar amount of the strong acid mixture relative to the volume of the liquid medium is 3 to 12 mol / L, for example 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, 9 mol / L, 10 mol / L, 11 mol / L or 12 mol / L.
[0027] In the present invention, the tantalum powder treated with strong acid and the tantalum carbide powder can generate tantalum metal ions, which can cooperate with the tantalum salt to provide tantalum metal ions, thereby forming a more stable metal organic framework structure with the ligand. The tantalum powder not treated with strong acid and the tantalum carbide powder are mainly physically mixed with the tantalum salt and the organic ligand source during the mixing process.
[0028] Preferably, in the liquid phase ball mill, the mass ratio of material, balls and liquid medium is 1:1:(0.8-1), for example 1:1:0.8, 1:1:0.83, 1:1:0.85, 1:1:0.9, 1:1:0.93, 1:1:0.95, 1:1:0.98 or 1:1:1, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0029] Preferably, the rotation speed of the liquid phase ball mill is 20-200r / min, for example 20r / min, 30r / min, 40r / min, 50r / min, 60r / min, 70r / min, 80r / min, 90r / min, 100r / min, 110r / min, 120r / min, 130r / min, 140r / min, 150r / min, 160r / min, 170r / min, 180r / min, 190r / min or 200r / min, and the time is 2-12h, for example 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0030] Preferably, the particle size of the ball-milled powder is 1 to 5 μm, for example, 1 μm, 1.3 μm, 1.5 μm, 1.8 μm, 2 μm, 2.3 μm, 2.5 μm, 2.8 μm, 3 μm, 3.3 μm, 3.5 μm, 3.8 μm, 4 μm, 4.3 μm, 4.5 μm, 4.8 μm or 5 μm, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0031] In the present invention, the material obtained after ball milling is subjected to particle size analysis (laser particle size analysis) and performance testing to continuously determine the final required particle size, and the particle size range obtained by ball milling is controlled to be 1 to 5 μm. The particles that do not meet the particle size requirements are graded and screened through an oscillating sieve to separate the particles that do not meet the requirements, and only the ball milled powder that meets the particle size requirements is retained.
[0032] As a preferred technical solution of the present invention, in step (1), the amount is controlled according to the ratio of the molar amount of tantalum element in the tantalum salt to the total molar amount of tantalum element in the tantalum powder and / or tantalum carbide powder (1-8):1, for example, 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1, 3:1, 3.3:1, 3.5:1, 3.8:1, 4:1, 4.3:1, 4.5:1, 4.8:1, 5:1, 5.3:1, 5.5:1, 5.8:1, 6:1, 6.3:1, 6.5:1, 6.8:1, 7:1, 7.3:1, 7.5:1, 7.8:1 or 8:1, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0033] Preferably, the tantalum salt is preliminarily subjected to a complex reaction with an organic ligand source to obtain an organic complex of tantalum, and then the organic complex of tantalum is mixed with the tantalum powder and / or tantalum carbide powder.
[0034] In the preparation method of the present invention, the tantalum salt and the organic ligand source may not react in advance, but are mixed with tantalum powder and / or tantalum carbide powder as raw materials at the same time. During the mixing process, the tantalum salt and the organic ligand form an organic complex of tantalum, and are evenly mixed with the tantalum powder and / or tantalum carbide powder. The one-time mixing and molding effect is better, and the preparation method is simpler and more convenient. Of course, it is also possible to first react the tantalum salt and the organic ligand source to form an organic complex of tantalum, which contains a metal-organic framework structure, and then mix it with tantalum powder and / or tantalum carbide powder, but the mixing process may destroy the already formed metal framework structure, affecting the porous effect.
[0035] Preferably, when the tantalum salt is preliminarily subjected to a complex reaction with an organic ligand source to obtain an organic complex of tantalum, the dosage is controlled according to the ratio of the molar amount of the tantalum element in the tantalum salt to the molar amount of the organic ligand source of 1:(1-2), for example, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9 or 1:2, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0036] Preferably, when the tantalum organic complex is used, the dosage is controlled according to the ratio of the molar amount of the tantalum element in the tantalum organic complex to the total molar amount of the tantalum element in the tantalum powder and / or tantalum carbide powder (1-8):1, for example, 1:1, 1.3:1, 1.5:1, 1.8:1, 2:1, 2.3:1, 2.5:1, 2.8:1, 3:1, 3.3:1, 3.5:1, 3.8:1, 4:1, 4.3:1, 4.5:1, 4.8:1, 5:1, 5.3:1, 5.5:1, 5.8:1, 6:1, 6.3:1, 6.5:1, 6.8:1, 7:1, 7.3:1, 7.5:1, 7.8:1 or 8:1, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0037] Preferably, the tantalum salt comprises tantalate and / or tantalum alkoxide.
[0038] Preferably, the tantalate comprises tantalum pentoxide and / or hydrated tantalate.
[0039] Preferably, the tantalum alkoxide includes at least one of tantalum methoxide, tantalum ethoxide or tantalum propoxide.
[0040] Preferably, the organic ligand source comprises a ligand comprising a carboxyl group.
[0041] In the present invention, it is preferred that the organic ligand source contains a carboxylic acid group, which can form a stable coordination bond with tantalum.
[0042] Preferably, the source of organic ligands comprises a dicarboxylic acid.
[0043] Preferably, the dicarboxylic acid comprises at least one of terephthalic acid, adipic acid or azelaic acid.
[0044] In the present invention, the organic ligand contained in the organic ligand source should have the ability to form a stable coordination bond with the tantalum metal ion, so that the obtained tantalum organic complex contains functional groups (such as carboxyl groups and alcohol groups) that can form coordination bonds with tantalum atoms, which helps to form a stable MOFs structure and facilitates subsequent rapid cooling, vacuum sintering and carbonization.
[0045] As a further preferred technical solution of the present invention, in step (1), during the mixing of the tantalum powder and / or tantalum carbide powder with the tantalum salt and the organic ligand source, a strong acid mixture is also added while the mixing is carried out.
[0046] In the present invention, in addition to the strong acid treatment during the ball milling stage of the tantalum powder and / or tantalum carbide powder, the strong acid treatment can also be performed for the first time or again during the mixing process to increase the tantalum metal ions, which is conducive to forming a stronger and more stable metal pore framework structure. Therefore, the strong acid mixture used in the two processes can be the same, that is, the whole strong acid mixture can be used in the ball milling stage after unified preparation, or the whole strong acid mixture can be used only in the mixing process, or it can be divided into two parts in any proportion and used in the two stages respectively.
[0047] As a preferred technical solution of the present invention, in step (1), during the mixing of the tantalum powder and / or tantalum carbide powder and the organic complex of tantalum, a dispersant is also added and mixed simultaneously.
[0048] Preferably, the dispersant comprises a silane coupling agent and / or carboxymethyl cellulose.
[0049] Preferably, the silane coupling agent includes at least one of KH-550, KH-560 or KH-570;
[0050] Preferably, the mass of the dispersant accounts for 1% to 5% of the total mass of the tantalum powder and / or tantalum carbide powder and tantalum organic complex, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, etc.
[0051] As a preferred technical solution of the present invention, in step (2), the suspension is rapidly cooled in a mold to obtain a molded solid.
[0052] The mold described in the present invention is designed according to the requirements of the crystal growth process and is designed in combination with the internal structure of the crystal growth furnace. The shape of the mold includes but is not limited to the above-mentioned shapes, and one-time molding can be achieved.
[0053] Preferably, the cooling medium used in the rapid cooling comprises liquid nitrogen.
[0054] In the present invention, the suspension is rapidly cooled by liquid nitrogen, and is rapidly frozen to below the eutectic point or the hypoeutectic point, and the temperature is below -40°C to -50°C, and the cooling time is shortened to avoid excessive growth and aggregation between particles; the rapid cooling can rapidly cool the mixed suspension into a solid, and prevent the solutes (tantalum salt, organic ligand source, organic complex of tantalum, tantalum powder and tantalum carbide powder, etc.) in the mixture from having enough time to diffuse and rearrange, and being frozen in a non-equilibrium structure, and the non-equilibrium structure is convenient for forming a porous structure in the subsequent high-temperature treatment process; compared with static pressure molding and then sintering, the problem of uneven pressure distribution that may occur in the molding process can be avoided, and the defects generated inside the material can be reduced to avoid affecting the mechanical properties and durability of the finished product.
[0055] Preferably, the rapid cooling temperature is -40 to -50°C, for example, -40°C, -41°C, -42°C, -43°C, -44°C, -45°C, -46°C, -47°C, -48°C, -49°C or -50°C, but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0056] Preferably, the shape of the mold includes any one of a cylindrical shape, a barrel shape, a tube shape or a rectangular parallelepiped.
[0057] As a preferred technical solution of the present invention, in step (3), the temperature of the vacuum sintering is 1000-2000°C, for example, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, 1900°C or 2000°C, and the time is 30-70h, for example, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h or 70h, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0058] As a preferred technical solution of the present invention, in step (4), the carbon source used for carbonization includes carbon powder.
[0059] Preferably, the carbonization further uses a supplementary carbon source, which includes CO gas and / or CH4 gas.
[0060] Preferably, the dosage is controlled according to the ratio of the molar amount of carbon in the supplementary carbon source to the molar amount of carbon in the carbon powder (0.1-0.2):1, for example, 0.1:1, 0.12:1, 0.14:1, 0.15:1, 0.17:1, 0.19:1 or 0.2:1, etc., but is not limited to the listed values, and other unlisted values within the above numerical range are also applicable.
[0061] Preferably, the amount of the porous body and the carbon powder is controlled according to the molar ratio of tantalum element to carbon element being 1:(1-1.1), for example, 1:1, 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09 or 1:1.1, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0062] In order to ensure that tantalum carbide with an atomic molar ratio of 1:1 is obtained and Ta2C is avoided, an excess of carbon powder can be added to ensure sufficient carbonization.
[0063] Preferably, the carbonization temperature is 2100-2300°C, for example, 2100°C, 2120°C, 2140°C, 2160°C, 2180°C, 2200°C, 2220°C, 2240°C, 2260°C, 2280°C or 2300°C, and the time is 10-70h, for example, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h or 70h, but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0064] As a preferred technical solution of the present invention, the preparation method of the porous tantalum carbide ceramic includes any one of the following technical solutions 1 to 8, which are arranged in descending order as follows:
[0065] Technical Solution 1: The preparation method of the porous tantalum carbide ceramic comprises:
[0066] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the carbon carbide powder to be 50% to 70%, placing them in a ball mill, adding liquid medium pure water, oxidant hydrogen peroxide and strong acid mixture, controlling the mass ratio of material, ball and liquid medium to be 1:1:(0.8-1), controlling the amount of hydrogen peroxide to be 5% to 20% of the mass of the liquid medium, controlling the amount of the strong acid mixture to be 3 to 12 mol / L relative to the volume of the liquid medium, performing high-energy liquid phase ball milling at a speed of 20 to 200 r / min for 2 to 12 hours, and obtaining ball milled powder with a uniform particle size of 1 to 5 μm; the strong acid mixture comprises a mixed acid solution of hydrofluoric acid and nitric acid;
[0067] The ball-milled powder, tantalum salt, organic ligand source and dispersant are mixed, and the amount is controlled according to the molar ratio of the tantalum salt to the tantalum element in the ball-milled powder being (1-8):1, and the molar ratio of the tantalum element in the tantalum salt to the organic ligand source being 1:(1-2), and the mass of the dispersant is controlled to account for 1% to 5% of the total mass of the ball-milled powder and the tantalum organic complex, so as to form a uniformly dispersed suspension;
[0068] The tantalum salt includes tantalate and / or tantalum alkoxide; the tantalate includes tantalum pentoxide and / or hydrated tantalate; the tantalum alkoxide includes at least one of tantalum methanol, tantalum ethoxide or tantalum propoxide; the ligand contained in the organic ligand source includes a carboxyl group; the organic ligand source includes a dicarboxylic acid; the dicarboxylic acid includes at least one of terephthalic acid, adipic acid or azelaic acid;
[0069] (2) placing the obtained suspension into a mold of a specific shape, wherein the specific shape includes any one of a cylindrical, barrel-shaped, tubular or rectangular parallelepiped shape, and rapidly cooling the suspension to -40 to -50°C using liquid nitrogen to obtain a molded solid;
[0070] (3) transferring the obtained shaped solid into a vacuum furnace, evacuating the vacuum and rapidly heating to 1000-2000° C., and sintering the shaped solid for 30-70 hours to obtain a porous body;
[0071] (4) Mixing the obtained porous body with carbon powder, controlling the amount of the porous body and the carbon powder according to the molar ratio of tantalum element to carbon element of 1:(1-1.1), slowly heating to 2100-2300° C. for carbonization for 10-70 hours, and then slowly cooling to prevent brittle cracking, to obtain porous tantalum carbide ceramics.
[0072] Technical Solution 2: Compared with Technical Solution 1, the adjustment content of Technical Solution 2 is that the strong acid mixture in step (1) is divided into two parts for use, and the specific adjustment is:
[0073] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 50% to 70%, placing them in a ball mill, adding liquid medium pure water, oxidant hydrogen peroxide and a first strong acid mixture, controlling the mass ratio of material, ball and liquid medium to be 1:1:(0.8-1), controlling the amount of hydrogen peroxide to be 5% to 20% of the mass of the liquid medium, performing high-energy liquid phase ball milling at a speed of 20 to 200 r / min for 2 to 12 hours, and obtaining a ball milled powder with a uniform particle size of 1 to 5 μm; the strong acid mixture includes a mixed acid solution of hydrofluoric acid and nitric acid;
[0074] The ball-milled powder, tantalum salt, organic ligand source, second strong acid mixture and dispersant are mixed, and the amount is controlled according to the molar ratio of the tantalum salt to the tantalum element in the ball-milled powder being (1-8):1, the molar ratio of the tantalum element in the tantalum salt to the molar ratio of the organic ligand source being 1:(1-2), and the mass of the dispersant is controlled to account for 1% to 5% of the total mass of the ball-milled powder and the tantalum organic complex, so as to form a uniformly dispersed suspension;
[0075] The total amount of the first strong acid mixture and the second strong acid mixture is controlled to be 3 to 12 mol / L relative to the volume of the liquid medium; the tantalum salt includes tantalate and / or tantalum alkoxide; the tantalate includes tantalum pentoxide and / or hydrated tantalum; the tantalum alkoxide includes at least one of tantalum methanol, tantalum ethoxide or tantalum propoxide; the ligand contained in the organic ligand source includes a carboxyl group; the organic ligand source includes a dicarboxylic acid; the dicarboxylic acid includes at least one of terephthalic acid, adipic acid or azelaic acid;
[0076] Step (2) to step (4) are consistent with technical solution 1.
[0077] Technical Solution 3: Compared with Technical Solution 1, the adjustment content of Technical Solution 3 is that the strong acid mixture in step (1) is not added during the grinding process of high-purity tantalum powder and tantalum carbide powder. The specific adjustment is:
[0078] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 50% to 70%, placing them in a ball ink tank, adding liquid medium pure water and oxidant hydrogen peroxide, controlling the mass ratio of the material, the ball and the liquid medium to be 1:1:(0.8-1), controlling the amount of the hydrogen peroxide to be 5% to 20% of the mass of the liquid medium, and performing high-energy liquid phase ball milling at a speed of 20 to 200 r / min for 2 to 12 hours to obtain a ball-milled powder with a uniform particle size of 1 to 5 μm;
[0079] Continue to add tantalum salt, organic ligand source, strong acid mixture and dispersant to the ball-milled powder, and mix them. The amount is controlled according to the molar ratio of the tantalum salt to the tantalum element in the high-purity carbon powder and tantalum carbide powder being (1-8):1, the ratio of the molar amount of the tantalum element in the tantalum salt to the molar amount of the organic ligand source being 1:(1-2), and the amount of the strong acid mixture is controlled to be 3-12 mol / L relative to the volume of the liquid medium, wherein the strong acid mixture includes a mixed acid solution of hydrofluoric acid and nitric acid; the mass of the dispersant is controlled to account for 1%-5% of the total mass of the ball-milled powder and the tantalum organic complex, so as to form a uniformly dispersed suspension;
[0080] The tantalum salt includes tantalate and / or tantalum alkoxide; the tantalate includes tantalum pentoxide and / or hydrated tantalate; the tantalum alkoxide includes at least one of tantalum methanol, tantalum ethoxide or tantalum propoxide; the ligand contained in the organic ligand source includes a carboxyl group; the organic ligand source includes a dicarboxylic acid; the dicarboxylic acid includes at least one of terephthalic acid, adipic acid or azelaic acid;
[0081] The preparation method of step (2) to step (4) is consistent with technical solution 1.
[0082] Technical Solution 4: Compared with Technical Solution 1, the adjustment content of Technical Solution 4 is that the strong acid mixture is not introduced in step (1), and the specific adjustment is:
[0083] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 50% to 70%, placing them in a ball mill, adding liquid medium pure water and oxidant hydrogen peroxide, controlling the mass ratio of material, ball and liquid medium to be 1:1:(0.8-1), controlling the amount of hydrogen peroxide to be 5% to 20% of the mass of the liquid medium, and performing high-energy liquid phase ball milling at a speed of 20 to 200 r / min for 2 to 12 hours to obtain ball milled powder with a uniform particle size of 1 to 5 μm;
[0084] The ball-milled powder, tantalum salt, organic ligand source and dispersant are mixed, and the amount is controlled according to the molar ratio of the tantalum salt to the tantalum element in the ball-milled powder being (1-8):1, the molar ratio of the tantalum element in the tantalum salt to the molar ratio of the organic ligand source being 1:(1-2), and the mass of the dispersant is controlled to account for 1% to 5% of the total mass of the ball-milled powder and the tantalum organic complex, so as to form a uniformly dispersed suspension;
[0085] The tantalum salt includes tantalate and / or tantalum alkoxide; the tantalate includes tantalum pentoxide and / or hydrated tantalate; the tantalum alkoxide includes at least one of tantalum methanol, tantalum ethoxide or tantalum propoxide; the ligand contained in the organic ligand source includes a carboxyl group; the organic ligand source includes a dicarboxylic acid; the dicarboxylic acid includes at least one of terephthalic acid, adipic acid or azelaic acid;
[0086] The preparation method of step (2) to step (4) is consistent with technical solution 1.
[0087] Technical Solution 5: Compared with Technical Solution 1, the adjustment content of Technical Solution 5 is that in step (1), the tantalum salt and the organic ligand source are first reacted to synthesize the organic complex of tantalum, and the specific adjustment is:
[0088] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 50% to 70%, placing them in a ball mill, adding liquid medium pure water, oxidant hydrogen peroxide and strong acid mixture, controlling the mass ratio of material, ball and liquid medium to be 1:1:(0.8-1), controlling the amount of hydrogen peroxide to be 5% to 20% of the mass of the liquid medium, controlling the amount of the strong acid mixture to be 3 to 12 mol / L relative to the volume of the liquid medium, performing high-energy liquid phase ball milling at a speed of 20 to 200 r / min for 2 to 12 hours, and obtaining a ball milled powder with a uniform particle size of 1 to 5 μm; the strong acid mixture comprises a mixed acid solution of hydrofluoric acid and nitric acid;
[0089] The ball-milled powder, the organic complex of tantalum and the dispersant are mixed, and the amount is controlled according to the molar ratio of the organic complex of tantalum to the tantalum element in the ball-milled powder being (1-8):1, and the mass of the dispersant is controlled to account for 1%-5% of the total mass of the ball-milled powder and the organic complex of tantalum to form a uniformly dispersed suspension;
[0090] The tantalum organic compound is obtained by complexing a tantalum salt with an organic ligand source, and the amount is controlled according to the ratio of the molar amount of the tantalum element in the tantalum salt to the molar amount of the organic ligand source of 1:(1-2); the tantalum salt includes tantalum acid salt and / or tantalum alcohol salt; the tantalum acid salt includes tantalum pentoxide and / or hydrated tantalum acid salt; the tantalum alcohol salt includes at least one of tantalum methanol, tantalum ethoxide or tantalum propoxide; the ligand contained in the organic ligand source includes a carboxyl group; the organic ligand source includes a dicarboxylic acid; the dicarboxylic acid includes at least one of terephthalic acid, adipic acid or azelaic acid;
[0091] The preparation method of step (2) to step (4) is consistent with technical solution 1.
[0092] Technical Solution 6: Compared with Technical Solution 1, the adjustment content of Technical Solution 6 is that in step (1), the tantalum salt and the organic ligand source are first reacted to synthesize the organic complex, and the strong acid mixture is used in two parts. The specific adjustment is:
[0093] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 50% to 70%, placing them in a ball mill, adding liquid medium pure water, oxidant hydrogen peroxide and a first strong acid mixture, controlling the mass ratio of material, ball and liquid medium to be 1:1:(0.8-1), controlling the amount of hydrogen peroxide to be 5% to 20% of the mass of the liquid medium, performing high-energy liquid phase ball milling at a speed of 20 to 200 r / min for 2 to 12 hours, and obtaining a ball milled powder with a uniform particle size of 1 to 5 μm; the strong acid mixture includes a mixed acid solution of hydrofluoric acid and nitric acid;
[0094] The ball-milled powder, the organic complex of tantalum, the second strong acid mixture and the dispersant are mixed, and the amount is controlled according to the molar ratio of the organic complex of tantalum to the tantalum element in the ball-milled powder being (1-8):1, and the mass of the dispersant is controlled to account for 1%-5% of the total mass of the ball-milled powder and the organic complex of tantalum to form a uniformly dispersed suspension;
[0095] The total amount of the strong acid mixture is controlled to be 3-12 mol / L relative to the volume of the liquid medium; the organic compound of tantalum is obtained by complexing a tantalum salt with an organic ligand source, and the amount is controlled according to the ratio of the molar amount of the tantalum element in the tantalum salt to the molar amount of the organic ligand source of 1:(1-2); the tantalum salt includes tantalate and / or tantalum alkoxide; the tantalate includes tantalum pentoxide and / or hydrated tantalum; the tantalum alkoxide includes at least one of tantalum methanol, tantalum ethoxide or tantalum propoxide; the ligand contained in the organic ligand source includes a carboxyl group; the organic ligand source includes a dicarboxylic acid; the dicarboxylic acid includes at least one of terephthalic acid, adipic acid or azelaic acid;
[0096] The preparation method of step (2) to step (4) is consistent with technical solution 1.
[0097] Technical Solution 7: Compared with Technical Solution 1, the adjustment content of Technical Solution 7 is that in step (1), the tantalum salt and the organic ligand source are first reacted to synthesize the organic complex, and the strong acid mixture is not added during the grinding process of the high-purity tantalum powder and the tantalum carbide powder. The specific technical solution is:
[0098] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 50% to 70%, placing them in a container, adding liquid medium pure water, oxidant hydrogen peroxide and a strong acid mixture, controlling the mass ratio of material, ball and liquid medium to be 1:1:(0.8-1), controlling the amount of hydrogen peroxide to be 5% to 20% of the mass of the liquid medium, and performing high-energy liquid phase ball milling at a speed of 20 to 200 r / min for 2 to 12 hours to obtain a ball-milled powder with a uniform particle size of 1 to 5 μm;
[0099] Continue to add tantalum organic complex, strong acid mixture and dispersant to the ball-milled powder, and control the amount of strong acid mixture to be 3-12 mol / L relative to the volume of liquid medium. The strong acid mixture includes a mixed acid solution of hydrofluoric acid and nitric acid. The amount is controlled according to the molar ratio of the tantalum organic complex to the tantalum element in the high-purity tantalum powder and tantalum carbide powder of (1-8):1. The mass of the dispersant is controlled to account for 1%-5% of the total mass of the ball-milled powder and the tantalum organic complex, so as to form a uniformly dispersed suspension;
[0100] The tantalum organic compound is obtained by complexing a tantalum salt with an organic ligand source, and the amount is controlled according to the ratio of the molar amount of the tantalum element in the tantalum salt to the molar amount of the organic ligand source of 1:(1-2); the tantalum salt includes tantalum acid salt and / or tantalum alcohol salt; the tantalum acid salt includes tantalum pentoxide and / or hydrated tantalum acid salt; the tantalum alcohol salt includes at least one of tantalum methanol, tantalum ethoxide or tantalum propoxide; the ligand contained in the organic ligand source includes a carboxyl group; the organic ligand source includes a dicarboxylic acid; the dicarboxylic acid includes at least one of terephthalic acid, adipic acid or azelaic acid;
[0101] The preparation method of step (2) to step (4) is consistent with technical solution 1.
[0102] Technical Solution 8: Compared with Technical Solution 1, the adjustment content of Technical Solution 8 is that in step (1), the tantalum salt and the organic ligand source are first reacted to synthesize the organic complex, and no strong acid mixture is introduced. The specific technical solution is:
[0103] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 50% to 70%, placing them in a ball mill, adding liquid medium pure water and oxidant hydrogen peroxide, controlling the mass ratio of material, ball and liquid medium to be 1:1:(0.8-1), controlling the amount of hydrogen peroxide to be 5% to 20% of the mass of the liquid medium, and performing high-energy liquid phase ball milling at a speed of 20 to 200 r / min for 2 to 12 hours to obtain ball milled powder with a uniform particle size of 1 to 5 μm;
[0104] The ball-milled powder, the organic complex of tantalum and the dispersant are mixed, and the amount is controlled according to the molar ratio of the organic complex of tantalum to the tantalum element in the ball-milled powder being (1-8):1, and the mass of the dispersant is controlled to account for 1%-5% of the total mass of the ball-milled powder and the organic complex of tantalum to form a uniformly dispersed suspension;
[0105] The tantalum organic compound is obtained by complexing a tantalum salt with an organic ligand source, and the amount is controlled according to the ratio of the molar amount of the tantalum element in the tantalum salt to the molar amount of the organic ligand source of 1:(1-2); the tantalum salt includes tantalum acid salt and / or tantalum alcohol salt; the tantalum acid salt includes tantalum pentoxide and / or hydrated tantalum acid salt; the tantalum alcohol salt includes at least one of tantalum methanol, tantalum ethoxide or tantalum propoxide; the ligand contained in the organic ligand source includes a carboxyl group; the organic ligand source includes a dicarboxylic acid; the dicarboxylic acid includes at least one of terephthalic acid, adipic acid or azelaic acid;
[0106] The preparation method of step (2) to step (4) is consistent with technical solution 1.
[0107] In the above technical solutions, technical solutions 1-4 are that the tantalum salt and the organic ligand source are not reacted in advance, but are mixed with tantalum powder and / or tantalum carbide powder as raw materials at the same time. During the mixing process, the tantalum salt and the organic ligand form an organic complex of tantalum, and are evenly mixed with the tantalum powder and / or tantalum carbide powder. The porous effect of the tantalum carbide ceramic formed by one-time mixing is better, and the preparation method is simpler and more convenient; among them, technical solutions 1-2 are all grinding high-purity tantalum powder and tantalum carbide powder with a strong acid mixture, which can introduce more tantalum ions and make the metal structure more stable. Technical solution 3 only introduces part of the strong acid to grind the high-purity tantalum powder and tantalum carbide powder. Technical solution 4 does not introduce the strong acid mixture spheroidal graphite, and the stability of the metal structure is slightly worse.
[0108] Technical solutions 5-8 choose to first react tantalum salt and organic ligand source to form an organic complex of tantalum, which contains a metal-organic framework structure, and then mix it with tantalum powder and / or tantalum carbide powder. The mixing process may destroy the already formed metal framework structure, which affects the porous effect of tantalum carbide ceramics compared with technical solutions 1-4; Technical solutions 5-6 both use a strong acid mixture to grind high-purity tantalum powder and tantalum carbide powder, which can introduce more tantalum ions and make the metal structure more stable. Technical solution 7 only introduces part of the strong acid to grind high-purity tantalum powder and tantalum carbide powder. Technical solution 8 does not introduce a strong acid mixture, and the stability of the metal structure is slightly worse.
[0109] In the present invention, after carbonization out of the furnace, the barrel-shaped and cylindrical finished products can be directly used in silicon carbide crystal growth, and the cylindrical and rectangular products can be cut into discs and plates by diamond wire for reuse.
[0110] In a second aspect, the present invention provides a porous tantalum carbide ceramic, wherein the porous tantalum carbide ceramic is obtained using the preparation method described in the first aspect.
[0111] As a preferred technical solution of the present invention, the porous tantalum carbide ceramic has disordered pores and ordered macroscopic pores;
[0112] Preferably, the pore size of the porous tantalum carbide ceramic is 1 to 100 μm, for example, it can be 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, 15 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm or 100 μm, etc., and the porosity is 10% to 60%, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or 60%, etc., but is not limited to the listed values, and other values not listed within the above numerical range are also applicable.
[0113] In a third aspect, the present invention provides an application of the porous tantalum carbide ceramic described in the second aspect, wherein the application includes using the porous tantalum carbide ceramic as a filter material when preparing silicon carbide single crystals.
[0114] Compared with the prior art solutions, the present invention has at least the following beneficial effects:
[0115] The preparation method of the present invention utilizes a tantalum salt and an organic ligand source to react with tantalum powder and / or tantalum carbide powder in a liquid phase system to obtain a metal organic framework structure, and the solid after rapid cooling is decomposed or volatilized at high temperature to achieve pore formation, so that the porous tantalum carbide ceramic has disordered micron-level pores. When the obtained porous tantalum carbide ceramic is used to prepare single-crystal silicon carbide by physical vapor deposition, compared with traditional porous graphite materials, it can allow gaseous substances generated by silicon carbide to pass through, and is resistant to high temperatures, has high strength, does not participate in reactions, does not produce defects such as impurities entering the crystal or forming inclusions, and effectively achieves filtering. BRIEF DESCRIPTION OF THE DRAWINGS
[0116] Figure 1 This is a surface photograph of the porous tantalum carbide ceramic obtained in Example 1. DETAILED DESCRIPTION
[0117] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0118] It should be clear to those skilled in the art that the embodiments are only intended to help understand the present invention and should not be considered as specific limitations of the present invention.
[0119] Example 1
[0120] This embodiment provides a method for preparing a porous tantalum carbide ceramic, the preparation method comprising:
[0121] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 60%, placing them in a ball mill, adding liquid medium pure water, oxidant hydrogen peroxide and strong acid mixture, controlling the mass ratio of material, ball and liquid medium to be 1:1:0.9, controlling the amount of hydrogen peroxide to be 10% of the mass of the liquid medium, controlling the amount of the strong acid mixture to be 6 mol / L relative to the volume of the liquid medium, performing high-energy liquid phase ball milling at a speed of 100 r / min for 6 h, and obtaining ball milled powder with uniform particle size of 1 to 5 μm; the strong acid mixture comprises a mixed acid solution of hydrofluoric acid and nitric acid;
[0122] The ball-milled powder, tantalum pentoxide, terephthalic acid and carboxymethyl cellulose are mixed, and the amount is controlled according to the molar ratio of the tantalum pentoxide to the tantalum element in the ball-milled powder being 5:1, and the amount is controlled according to the molar ratio of the tantalum element in the tantalum pentoxide to the molar amount of terephthalic acid being 1:1, and the mass of the carboxymethyl cellulose is controlled to account for 3% of the total mass of the ball-milled powder and the tantalum organic complex, to form a uniformly dispersed suspension;
[0123] (2) pouring the obtained suspension into a mold of a specific shape, wherein the specific shape includes any one of a cylindrical shape, a barrel shape, a tube shape or a rectangular parallelepiped shape, and rapidly cooling the suspension to -45°C using liquid nitrogen to obtain a molded solid;
[0124] (3) transferring the obtained shaped solid into a vacuum furnace, evacuating the vacuum and rapidly heating to 1500° C., and sintering the shaped solid for 50 h to obtain a porous body;
[0125] (4) The obtained porous body is mixed with carbon powder, and the amount of the porous body and the carbon powder is controlled according to the molar ratio of tantalum element to carbon element of 1:1, and the temperature is slowly raised to 2100°C for carbonization for 50 hours, and then the temperature is slowly lowered to prevent brittle cracking, so as to obtain a porous tantalum carbide ceramic.
[0126] Example 2
[0127] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 60%, placing them in a ball mill, adding liquid medium pure water, oxidant hydrogen peroxide and a first strong acid mixture, controlling the mass ratio of material, ball and liquid medium to be 1:1:0.9, controlling the amount of hydrogen peroxide to be 10% of the mass of the liquid medium, performing high-energy liquid phase ball milling at a speed of 100 r / min for 6 hours, and obtaining a ball milled powder with a uniform particle size of 1 to 5 μm; the strong acid mixture includes a mixed acid solution of hydrofluoric acid and nitric acid;
[0128] The ball-milled powder, tantalum pentoxide, terephthalic acid, a second strong acid mixture and carboxymethyl cellulose are mixed, and the amount is controlled according to the molar ratio of the tantalum pentoxide to the tantalum element in the ball-milled powder being 5:1, and the amount is controlled according to the molar ratio of the tantalum element in the tantalum pentoxide to the molar amount of terephthalic acid being 1:1, and the mass of the carboxymethyl cellulose is controlled to account for 3% of the total mass of the ball-milled powder and the tantalum organic complex to form a uniformly dispersed suspension; the overall amount of the first strong acid mixture and the second strong acid mixture is controlled to be 6 mol / L relative to the volume of the liquid medium;
[0129] (2) pouring the obtained suspension into a mold of a specific shape, wherein the specific shape includes any one of a cylindrical shape, a barrel shape, a tube shape or a rectangular parallelepiped shape, and rapidly cooling the suspension to -45°C using liquid nitrogen to obtain a molded solid;
[0130] (3) transferring the obtained shaped solid into a vacuum furnace, evacuating the vacuum and rapidly heating to 1500° C., and sintering the shaped solid for 50 h to obtain a porous body;
[0131] (4) The obtained porous body is mixed with carbon powder, and the amount of the porous body and the carbon powder is controlled according to the molar ratio of tantalum element to carbon element of 1:1, and the temperature is slowly raised to 2100°C for carbonization for 50 hours, and then the temperature is slowly lowered to prevent brittle cracking, so as to obtain a porous tantalum carbide ceramic.
[0132] Example 3
[0133] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 60%, putting them into a spherical ink tank, adding liquid medium pure water and oxidant hydrogen peroxide, controlling the mass ratio of material, ball and liquid medium to be 1:1:0.9, controlling the amount of hydrogen peroxide to be 10% of the mass of the liquid medium, and mixing the above mixture evenly; performing high-energy liquid phase ball milling at a speed of 100 r / min for 6 hours to obtain a ball-milled powder with a uniform particle size of 1 to 5 μm;
[0134] Continue to add tantalum pentoxide, terephthalic acid, carboxymethyl cellulose and a strong acid mixture to the ball-milled powder, and mix them. The amount of the strong acid mixture is controlled to be 6 mol / L relative to the volume of the liquid medium, and the strong acid mixture includes a mixed acid solution of hydrofluoric acid and nitric acid; the amount is controlled according to a molar ratio of 5:1 between the tantalum salt and the tantalum element in the high-purity tantalum powder and the tantalum carbide powder, and the amount is controlled according to a ratio of 1:1 between the molar amount of the tantalum element in tantalum pentoxide and the molar amount of terephthalic acid, and the mass of the carboxymethyl cellulose is controlled to account for 3% of the total mass of the ball-milled powder and the tantalum organic complex, so as to form a uniformly dispersed suspension;
[0135] (2) pouring the obtained suspension into a mold of a specific shape, wherein the specific shape includes any one of a cylindrical shape, a barrel shape, a tube shape or a rectangular parallelepiped shape, and rapidly cooling the suspension to -45°C using liquid nitrogen to obtain a molded solid;
[0136] (3) transferring the obtained shaped solid into a vacuum furnace, evacuating the vacuum and rapidly heating to 1500° C., and sintering the shaped solid for 50 h to obtain a porous body;
[0137] (4) The obtained porous body is mixed with carbon powder, and the amount of the porous body and the carbon powder is controlled according to the molar ratio of tantalum element to carbon element of 1:1, and the temperature is slowly raised to 2100°C for carbonization for 50 hours, and then the temperature is slowly lowered to prevent brittle cracking, so as to obtain a porous tantalum carbide ceramic.
[0138] Example 4
[0139] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 60%, placing them in a ball mill, adding liquid medium pure water and oxidant hydrogen peroxide, controlling the mass ratio of material, ball and liquid medium to be 1:1:0.9, controlling the amount of hydrogen peroxide to be 10% of the mass of the liquid medium, and performing high-energy liquid phase ball milling at a speed of 100 r / min for 6 hours to obtain ball-milled powder with a uniform particle size of 1 to 5 μm;
[0140] The ball-milled powder, tantalum pentoxide, terephthalic acid and carboxymethyl cellulose are mixed, and the amount is controlled according to the molar ratio of the tantalum pentoxide to the tantalum element in the ball-milled powder being 5:1, and the amount is controlled according to the molar ratio of the tantalum element in the tantalum pentoxide to the molar ratio of terephthalic acid being 1:1, and the mass of the dispersant is controlled to account for 3% of the total mass of the ball-milled powder and the tantalum organic complex, so as to form a uniformly dispersed suspension;
[0141] (2) pouring the obtained suspension into a mold of a specific shape, wherein the specific shape includes any one of a cylindrical shape, a barrel shape, a tube shape or a rectangular parallelepiped shape, and rapidly cooling the suspension to -45°C using liquid nitrogen to obtain a molded solid;
[0142] (3) transferring the obtained shaped solid into a vacuum furnace, evacuating the vacuum and rapidly heating to 1500° C., and sintering the shaped solid for 50 h to obtain a porous body;
[0143] (4) The obtained porous body is mixed with carbon powder, and the amount of the porous body and the carbon powder is controlled according to the molar ratio of tantalum element to carbon element of 1:1, and the temperature is slowly raised to 2100°C for carbonization for 50 hours, and then the temperature is slowly lowered to prevent brittle cracking, so as to obtain a porous tantalum carbide ceramic.
[0144] Example 5
[0145] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 50%, placing them in a ball mill, adding liquid medium pure water, oxidant hydrogen peroxide and strong acid mixture, controlling the mass ratio of material, ball and liquid medium to be 1:1:0.8, controlling the amount of hydrogen peroxide to be 5% of the mass of the liquid medium, controlling the amount of the strong acid mixture to be 3 mol / L relative to the volume of the liquid medium, performing high-energy liquid phase ball milling at a speed of 20 r / min for 12 h, and obtaining a ball milled powder with a uniform particle size of 1 to 5 μm; the strong acid mixture comprises a mixed acid solution of hydrofluoric acid and nitric acid;
[0146] The ball-milled powder, an organic complex of tantalum (formed by complexation reaction of tantalum ethoxide and azelaic acid, the amount of which is controlled according to the ratio of the molar amount of tantalum element in tantalum ethoxide to the molar amount of azelaic acid of 1:1) and a dispersant silane coupling agent KH-560 are mixed, and the amount of which is controlled according to the molar ratio of the organic complex of tantalum to the tantalum element in the ball-milled powder of 3:1, and the mass of the dispersant is controlled to account for 1% of the total mass of the ball-milled powder and the organic complex of tantalum, to form a uniformly dispersed suspension;
[0147] (2) pouring the obtained suspension into a mold of a specific shape, wherein the specific shape includes any one of a cylindrical shape, a barrel shape, a tube shape or a rectangular parallelepiped shape, and rapidly cooling the suspension to -42°C using liquid nitrogen to obtain a molded solid;
[0148] (3) transferring the obtained shaped solid into a vacuum furnace, evacuating the vacuum and rapidly heating to 1600° C., and sintering the shaped solid for 70 hours to obtain a porous body;
[0149] (4) The obtained porous body is mixed with carbon powder, and the amount of the porous body and the carbon powder is controlled according to the molar ratio of tantalum element to carbon element of 1:1.1, and the temperature is slowly raised to 2300° C. for carbonization for 10 hours, and then the temperature is slowly lowered to prevent brittle cracking, so as to obtain a porous tantalum carbide ceramic.
[0150] Example 6
[0151] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 50%, placing them in a ball mill, adding liquid medium pure water, oxidant hydrogen peroxide and a first strong acid mixture, controlling the mass ratio of material, ball and liquid medium to be 1:1:0.8, controlling the amount of hydrogen peroxide to be 5% of the mass of the liquid medium, performing high-energy liquid phase ball milling at a speed of 20 r / min for 12 h, and obtaining a ball milled powder with a uniform particle size of 1 to 5 μm; the strong acid mixture includes a mixed acid solution of hydrofluoric acid and nitric acid;
[0152] The ball-milled powder, an organic complex of tantalum (formed by complexation reaction of tantalum ethoxide and azelaic acid, the dosage is controlled according to the ratio of the molar amount of tantalum element in tantalum ethoxide to the molar amount of azelaic acid of 1:1), a second strong acid mixture and a dispersant silane coupling agent KH-560, the dosage is controlled according to the molar ratio of the organic complex of tantalum to the tantalum element in the ball-milled powder of 3:1, the mass of the dispersant is controlled to account for 1% of the total mass of the ball-milled powder and the organic complex of tantalum, to form a uniformly dispersed suspension; the overall dosage of the strong acid mixture is controlled to be 3 mol / L relative to the volume of the liquid medium;
[0153] (2) pouring the obtained suspension into a mold of a specific shape, wherein the specific shape includes any one of a cylindrical shape, a barrel shape, a tube shape or a rectangular parallelepiped shape, and rapidly cooling the suspension to -42°C using liquid nitrogen to obtain a molded solid;
[0154] (3) transferring the obtained shaped solid into a vacuum furnace, evacuating the vacuum and rapidly heating to 1600° C., and sintering the shaped solid for 70 hours to obtain a porous body;
[0155] (4) The obtained porous body is mixed with carbon powder, and the amount of the porous body and the carbon powder is controlled according to the molar ratio of tantalum element to carbon element of 1:1.1, and the temperature is slowly raised to 2300° C. for carbonization for 10 hours, and then the temperature is slowly lowered to prevent brittle cracking, so as to obtain a porous tantalum carbide ceramic.
[0156] Example 7
[0157] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 50%, placing them in a spherical ink tank, adding liquid medium pure water and oxidant hydrogen peroxide, controlling the mass ratio of the material, the ball and the liquid medium to be 1:1:0.8, and controlling the amount of the hydrogen peroxide to be 5% of the mass of the liquid medium; performing high-energy liquid phase ball milling at a speed of 20 r / min for 12 hours to obtain a ball-milled powder with a uniform particle size of 1 to 5 μm;
[0158] Adding an organic complex of tantalum (formed by complexation reaction of tantalum ethoxide and azelaic acid, the amount is controlled according to the ratio of the molar amount of tantalum element in tantalum ethoxide to the molar amount of azelaic acid of 1:1), a dispersant silane coupling agent KH-560 and a strong acid mixture to the ball-milled powder, and controlling the amount of the strong acid mixture to be 3 mol / L relative to the volume of the liquid medium. The strong acid mixture includes a mixed acid solution of hydrofluoric acid and nitric acid, and the amount is controlled according to the molar ratio of the organic complex of tantalum to the tantalum element in high-purity tantalum powder and tantalum carbide powder of 3:1. The mass of the dispersant silane coupling agent KH-560 is controlled to account for 1% of the total mass of the ball-milled powder and the organic complex of tantalum, so as to form a uniformly dispersed suspension;
[0159] (2) pouring the obtained suspension into a mold of a specific shape, wherein the specific shape includes any one of a cylindrical shape, a barrel shape, a tube shape or a rectangular parallelepiped shape, and rapidly cooling the suspension to -42°C using liquid nitrogen to obtain a molded solid;
[0160] (3) transferring the obtained shaped solid into a vacuum furnace, evacuating the vacuum and rapidly heating to 1600° C., and sintering the shaped solid for 70 hours to obtain a porous body;
[0161] (4) The obtained porous body is mixed with carbon powder, and the amount of the porous body and the carbon powder is controlled according to the molar ratio of tantalum element to carbon element of 1:1.1, and the temperature is slowly raised to 2300° C. for carbonization for 10 hours, and then the temperature is slowly lowered to prevent brittle cracking, so as to obtain a porous tantalum carbide ceramic.
[0162] Example 8
[0163] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the tantalum carbide powder to be 50%, placing them in a ball mill, adding liquid medium pure water and oxidant hydrogen peroxide, controlling the mass ratio of material, ball and liquid medium to be 1:1:0.8, controlling the amount of hydrogen peroxide to be 5% of the mass of the liquid medium, and performing high-energy liquid phase ball milling at a speed of 20 r / min for 12 h to obtain ball milled powder with a uniform particle size of 1 to 5 μm;
[0164] The ball-milled powder, an organic complex of tantalum (formed by complexation reaction of tantalum ethoxide and azelaic acid, the amount of which is controlled according to the ratio of the molar amount of tantalum element in tantalum ethoxide to the molar amount of azelaic acid of 1:1) and a dispersant silane coupling agent KH-560 are mixed, and the amount of which is controlled according to the molar ratio of the organic complex of tantalum to the tantalum element in the ball-milled powder of 3:1, and the mass of the dispersant is controlled to account for 1% of the total mass of the ball-milled powder and the organic complex of tantalum, to form a uniformly dispersed suspension;
[0165] (2) pouring the obtained suspension into a mold of a specific shape, wherein the specific shape includes any one of a cylindrical shape, a barrel shape, a tube shape or a rectangular parallelepiped shape, and rapidly cooling the suspension to -42°C using liquid nitrogen to obtain a molded solid;
[0166] (3) transferring the obtained shaped solid into a vacuum furnace, evacuating the vacuum and rapidly heating to 1600° C., and sintering the shaped solid for 70 hours to obtain a porous body;
[0167] (4) The obtained porous body is mixed with carbon powder, and the amount of the porous body and the carbon powder is controlled according to the molar ratio of tantalum element to carbon element of 1:1.1, and the temperature is slowly raised to 2300° C. for carbonization for 10 hours, and then the temperature is slowly lowered to prevent brittle cracking, so as to obtain a porous tantalum carbide ceramic.
[0168] Example 9
[0169] (1) Weighing high-purity tantalum powder and tantalum carbide powder, controlling the mass proportion of the carbon carbide powder to be 60%, placing them in a ball mill, adding liquid medium pure water, oxidant hydrogen peroxide and strong acid mixture, controlling the mass ratio of material, ball and liquid medium to be 1:1:1, controlling the amount of hydrogen peroxide to be 20% of the mass of the liquid medium, controlling the amount of the strong acid mixture to be 12 mol / L relative to the volume of the liquid medium, performing high-energy liquid phase ball milling at a speed of 200 r / min for 2 h, and obtaining ball milled powder with uniform particle size of 1 to 5 μm; the strong acid mixture comprises a mixed acid solution of hydrofluoric acid and nitric acid;
[0170] The ball-milled powder, hydrated tantalate, adipic acid and carboxymethyl cellulose are mixed, and the amount is controlled according to the molar ratio of the hydrated tantalate to the tantalum element in the ball-milled powder being 6:1, and the amount is controlled according to the molar ratio of the tantalum element in tantalum pentoxide to the molar ratio of terephthalic acid being 1:1.5, and the mass of the dispersant is controlled to account for 5% of the total mass of the ball-milled powder and the tantalum organic complex, so as to form a uniformly dispersed suspension;
[0171] (2) pouring the obtained suspension into a mold of a specific shape, wherein the specific shape includes any one of a cylindrical shape, a barrel shape, a tube shape or a rectangular parallelepiped shape, and rapidly cooling the suspension to -45°C using liquid nitrogen to obtain a molded solid;
[0172] (3) transferring the obtained shaped solid into a vacuum furnace, evacuating the vacuum and rapidly heating to 1800° C., and sintering the shaped solid for 30 hours to obtain a porous body;
[0173] (4) The obtained porous body is mixed with carbon powder, and the amount of the porous body and the carbon powder is controlled according to the molar ratio of tantalum element to carbon element of 1: (1-1.1), and the temperature is slowly raised to 2200°C for carbonization for 10 hours. During the carbonization process, a carbon source CH4 gas is added, and the amount is controlled according to the ratio of the molar amount of carbon in CH4 to the molar amount of carbon in the carbon powder of 0.1:1, and then the temperature is slowly lowered to prevent brittle cracking, thereby obtaining a porous tantalum carbide ceramic.
[0174] Example 10
[0175] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (1) of the preparation method, only high-purity tantalum powder is used instead of tantalum carbide powder. Except for the above, other conditions are exactly the same as those in Example 1.
[0176] Embodiment 11
[0177] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (1) of the preparation method, only tantalum carbide powder is used instead of high-purity tantalum powder. Except for the above, other conditions are exactly the same as those in Example 1.
[0178] Example 12
[0179] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (1) of the preparation method, the molar ratio of tantalum element in tantalum pentoxide to tantalum element in ball-milled powder is adjusted from 5:1 to 1:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0180] Example 13
[0181] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (1) of the preparation method, the molar ratio of tantalum element in tantalum pentoxide to tantalum element in ball-milled powder is adjusted from 5:1 to 8:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0182] Embodiment 14
[0183] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (1) of the preparation method, the molar ratio of tantalum element in tantalum pentoxide to tantalum element in ball-milled powder is adjusted from 5:1 to 0.5:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0184] Embodiment 15
[0185] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (1) of the preparation method, the molar ratio of tantalum element in tantalum pentoxide to tantalum element in ball-milled powder is adjusted from 5:1 to 9:1. Except for the above, other conditions are exactly the same as those in Example 1.
[0186] Example 16
[0187] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (2) of the preparation method, the temperature reached by rapid cooling is adjusted from -45°C to -50°C. Except for the above, other conditions are exactly the same as those in Example 1.
[0188] Embodiment 17
[0189] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (2) of the preparation method, the temperature reached by rapid cooling is adjusted from -45°C to -40°C. Except for the above, other conditions are exactly the same as those in Example 1.
[0190] Embodiment 18
[0191] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (2) of the preparation method, the temperature reached by rapid cooling is adjusted from -45°C to -30°C. Except for the above, other conditions are exactly the same as those in Example 1.
[0192] Embodiment 19
[0193] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (2) of the preparation method, the temperature reached by rapid cooling is adjusted from -45°C to -10°C. Except for the above, other conditions are exactly the same as those in Example 1.
[0194] Embodiment 20
[0195] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (3) of the preparation method, the temperature of vacuum sintering is adjusted from 1500° C. to 900° C. Except for the above, other conditions are exactly the same as those in Example 1.
[0196] Embodiment 21
[0197] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (3) of the preparation method, the temperature of vacuum sintering is adjusted from 1500° C. to 1000° C. Except for the above, other conditions are exactly the same as those in Example 1.
[0198] Embodiment 22
[0199] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (3) of the preparation method, the temperature of vacuum sintering is adjusted from 1500° C. to 2000° C. Except for the above, other conditions are exactly the same as those in Example 1.
[0200] Embodiment 23
[0201] This embodiment provides a method for preparing porous tantalum carbide ceramics. In step (3) of the preparation method, the temperature of vacuum sintering is adjusted from 1500° C. to 2100° C. Except for the above, other conditions are exactly the same as those in Example 1.
[0202] Comparative Example 1
[0203] This comparative example provides a method for preparing a porous tantalum carbide ceramic. The preparation method does not prepare a suspension, and does not use the suspension to cool to obtain a shaped solid. Steps (1) and (2) of the preparation method are replaced by mixing the obtained ball-milled powder, an organic complex of tantalum and a dispersant in a solid phase, and then using an isostatic pressing method to obtain a shaped solid. Except for the above, other conditions are exactly the same as those in Example 1.
[0204] Comparative Example 2
[0205] This comparative example provides a method for preparing tantalum carbide ceramics. In step (1) of the preparation method, no organic complex of tantalum is used, and the organic complex of tantalum is replaced by an equal amount of ball-milled powder. Except for the above, other conditions are exactly the same as those in Example 1.
[0206] Comparative Example 3
[0207] This comparative example provides a method for preparing tantalum carbide ceramics. In step (2) of the preparation method, rapid cooling is not performed, but natural cooling to room temperature is adopted, and then cooling to -5°C is adopted to obtain a molded solid. Except for the above, other conditions are exactly the same as those in Example 1.
[0208] Comparative Example 4
[0209] This comparative example provides a method for preparing tantalum carbide ceramics. In step (3) of the preparation method, sintering is performed in an inert atmosphere without vacuuming. Except for the above, other conditions are exactly the same as those in Example 1.
[0210] The tantalum carbide ceramics obtained in the examples and comparative examples are used as filter materials in preparing single-crystalline silicon carbide by physical vapor deposition. The specific method for preparing single-crystalline silicon carbide includes:
[0211] (1) Place silicon carbide powder at the bottom of the inner cavity of the crucible, flatten and compact it, place tantalum carbide ceramic on top of the silicon carbide powder, and snap the crucible cover with the seed crystal fixed on it to seal it;
[0212] (2) Place in the growth furnace and evacuate to less than 10 -2 Pa, then fill with protective gas to 500mbar;
[0213] (3) Using an induction coil to heat to 2200°C, the pressure was reduced to 5 mbar, and the silicon carbide crystal was grown for 120 hours;
[0214] (4) Filling with protective gas and cooling to obtain silicon carbide crystals.
[0215] The obtained silicon carbide single crystal was inspected for defects using a silicon carbide substrate defect inspection device. The inspection indicators were inclusions (pieces / piece), microtubes (pieces / cm 2 ), the fewer the inclusions and microtubes, the better the quality of the silicon carbide single crystal. The test data are as follows:
[0216] Serial number Package(piece / piece) <![CDATA[Total dislocation (number / cm 2 )]]> Example 1 1 502 Example 2 1 503 Example 3 1 505 Example 4 1 506 Example 5 2 510 Example 6 3 512 Example 7 3 513 Example 8 4 515 Example 9 1 504 Example 10 4 518 Embodiment 11 5 517 Example 12 6 525 Example 13 6 525 Embodiment 14 7 527 Embodiment 15 7 528 Example 16 6 522 Embodiment 17 7 523 Embodiment 18 7 525 Embodiment 19 7 526 Embodiment 20 7 523 Embodiment 21 7 519 Embodiment 22 7 524 Embodiment 23 7 525 Comparative Example 1 32 785 Comparative Example 2 41 810 Comparative Example 3 30 805 Comparative Example 4 35 825
[0217] From the above data, we can see that:
[0218] In Examples 1-4, the tantalum salt and the organic ligand source may not be reacted in advance, but may be mixed with tantalum powder and / or tantalum carbide powder as raw materials at the same time for one-time mixed molding, and the porous effect is better. For example, the surface of the porous silicon carbide ceramic obtained in Example 1 ( Figure 1 ); In Examples 5-8, the tantalum salt and the organic ligand source are first reacted to form an organic complex of tantalum. The inclusions and total dislocation properties of the silicon carbide crystals in the porous silicon carbide ceramics prepared in Examples 1-4 are better than those in Examples 5-8;
[0219] In Examples 1-4, the strong acid mixture in Example 1 is added during the process of tantalum powder and / or tantalum carbide powder spheroidal graphite, more tantalum ions are introduced into the system, and the metal structure is more stable, so the inclusion and total dislocation performance of Example 1 are better than those of Examples 2-4;
[0220] In Examples 5-8, the strong acid mixture in Example 5 is added during the process of tantalum powder and / or tantalum carbide powder spheroidal graphite, more tantalum ions are introduced into the system, and the metal structure is more stable, so the inclusion and total dislocation performance of Example 1 are better than those of Examples 6-8;
[0221] Examples 10-11 are based on Example 1, but only tantalum powder or tantalum carbide powder is introduced separately, and the inclusion and total dislocation performance are inferior to those of Example 1;
[0222] Examples 12-15 adjust the usage ratio of tantalum salt to tantalum powder and tantalum carbide powder, Examples 16-19 adjust the rapid cooling temperature, and Examples 20-23 adjust the sintering temperature. The defect index of the silicon carbide crystal finally prepared is slightly worse than that of Examples 1-8.
[0223] In parallel comparison with Example 1, the technical scheme of Example 1 did not prepare a suspension, and adopted an isostatic pressing method; Example 2 abandoned the introduction of an organic complex of tantalum; Example 3 did not adopt a rapid cooling method; and Example 4 did not perform vacuum sintering under vacuum conditions, which ultimately led to a significant increase in the inclusions and total dislocations of the silicon carbide crystals.
[0224] From the above, it can be seen that the present invention obtains porous tantalum carbide ceramics by mixing tantalum powder and / or tantalum carbide powder with an organic complex of tantalum in a liquid phase system, rapidly cooling the mixture to form a solid, vacuum sintering the obtained solid, and then carbonizing it. In the preparation method, the organic complex of tantalum provides a ligand to form a metal organic framework structure with tantalum, adjust the porosity and distribution, and further decompose or volatilize at high temperature to achieve pore formation. The porous silicon carbide ceramics finally prepared have disordered micron-sized pores. When used in the preparation of single-crystal silicon carbide by physical vapor deposition, compared with traditional graphite materials, it can allow gaseous substances generated by silicon carbide to pass through, and can withstand high temperatures, and has high strength, does not participate in the reaction, does not produce impurities entering the crystal or forming defects such as carbon encapsulation, and effectively achieves filtering.
[0225] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0226] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0227] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing porous tantalum carbide ceramics, characterized in that: The preparation method comprises: (1) mixing tantalum powder and / or tantalum carbide powder with tantalum salt and an organic ligand source to generate a reactant with a metal organic framework structure to obtain a suspension; (2) rapidly cooling the suspension to obtain a solid; (3) sintering the solid under vacuum to obtain a porous body; (4) Carbonizing the porous body to obtain porous tantalum carbide ceramics.
2. The preparation method according to claim 1, characterized in that: In step (1), tantalum powder and / or tantalum carbide powder is firstly ball-milled to obtain ball-milled powder, and then the obtained ball-milled powder is mixed with the tantalum salt and the organic ligand source.
3. The preparation method according to claim 2, characterized in that: The tantalum powder and the tantalum carbide powder are used simultaneously, and the mass proportion of the tantalum carbide powder is controlled to be 50% to 70%.
4. The preparation method according to claim 2, characterized in that: The ball milling includes liquid phase ball milling, and the liquid medium used in the liquid phase ball milling includes water.
5. The preparation method according to claim 4, characterized in that: The liquid phase ball milling also uses an oxidant, which includes hydrogen peroxide with a concentration of 25% to 35%.
6. The preparation method according to claim 5, characterized in that: The amount of hydrogen peroxide used is 5% to 20% of the mass of the liquid medium.
7. The preparation method according to claim 4, characterized in that: The liquid phase ball milling also uses a strong acid mixture.
8. The preparation method according to claim 7, characterized in that: The strong acid mixture includes a mixture of hydrofluoric acid and nitric acid.
9. The preparation method according to claim 7, characterized in that: The molar amount of the strong acid mixture relative to the volume of the liquid medium is 3-12 mol / L.
10. The preparation method according to claim 4, characterized in that: In the liquid phase ball mill, the mass ratio of material, balls and liquid medium is 1:1:(0.8~1).
11. The preparation method according to claim 4, characterized in that: The liquid phase ball mill has a rotation speed of 20-200 r / min and a time of 2-12 h.
12. The preparation method according to claim 2, characterized in that: The particle size of the ball-milled powder is 1-5 μm.
13. The preparation method according to claim 1, characterized in that: In step (1), the dosage is controlled according to the ratio of the molar amount of the tantalum element in the tantalum salt to the total molar amount of the tantalum element in the tantalum powder and / or tantalum carbide powder (1-8):
1.
14. The preparation method according to claim 2, characterized in that: The tantalum salt is preliminarily subjected to a complex reaction with an organic ligand source to obtain an organic complex of tantalum, and then the organic complex of tantalum is mixed with the tantalum powder and / or tantalum carbide powder.
15. The preparation method according to claim 1, characterized in that: The tantalum salt includes tantalate and / or tantalum alkoxide.
16. The preparation method according to claim 15, characterized in that: The tantalate includes hydrated tantalate.
17. The preparation method according to claim 15, characterized in that: The tantalum alkoxide includes at least one of tantalum methoxide, tantalum ethoxide or tantalum propoxide.
18. The preparation method according to claim 1, characterized in that: The organic ligand source contains a ligand including a carboxyl group.
19. The preparation method according to claim 18, characterized in that: The source of organic ligands includes dicarboxylic acids.
20. The preparation method according to claim 19, characterized in that: The dicarboxylic acid includes at least one of terephthalic acid, adipic acid or azelaic acid.
21. The preparation method according to claim 1, characterized in that: In step (1), during the mixing of the tantalum powder and / or tantalum carbide powder with the tantalum salt and the organic ligand source, a strong acid mixture is also added while the mixing is being performed.
22. The preparation method according to claim 1, characterized in that: In step (1), during the mixing of the tantalum powder and / or tantalum carbide powder with the tantalum salt and the organic ligand source, a dispersant is also added and mixed simultaneously.
23. The preparation method according to claim 22, characterized in that: The dispersant includes a silane coupling agent and / or carboxymethyl cellulose.
24. The preparation method according to claim 23, characterized in that: The silane coupling agent includes at least one of KH-550, KH-560 or KH-570.
25. The preparation method according to claim 22, characterized in that: The mass of the dispersant accounts for 1% to 5% of the total mass of the tantalum powder and / or tantalum carbide powder and the tantalum organic complex.
26. The preparation method according to claim 1, characterized in that: In step (2), the suspension is rapidly cooled in a mold to obtain a molded solid.
27. The preparation method according to claim 26, characterized in that: The cooling medium used in the rapid cooling includes liquid nitrogen.
28. The preparation method according to claim 26, characterized in that: The rapid cooling temperature is -40~-50°C.
29. The preparation method according to claim 26, characterized in that: The shape of the mold includes any one of a cylindrical shape and a rectangular parallelepiped shape.
30. The preparation method according to claim 1, characterized in that: In step (3), the vacuum sintering temperature is 1000-2000°C and the time is 30-70 hours.
31. The preparation method according to claim 1, characterized in that: In step (4), the carbon source used in the carbonization includes carbon powder.
32. The preparation method according to claim 1, characterized in that: The carbonization also uses a supplemental carbon source, which includes CO gas and / or CH4 gas.
33. The preparation method according to claim 31, characterized in that: The amount of the porous body and the carbon powder is controlled according to the molar ratio of tantalum element to carbon element being 1:(1-1.1).
34. The preparation method according to claim 1, characterized in that: The carbonization temperature is 2100-2300° C. and the time is 10-70 hours.
35. A porous tantalum carbide ceramic, characterized in that: Obtained using the preparation method described in any one of claims 1 to 34.
36. The porous tantalum carbide ceramic according to claim 35, characterized in that: The porous tantalum carbide ceramic has a pore size of 1-100 μm and a porosity of 10%-60%.
37. An application of the porous tantalum carbide ceramic according to claim 35 or 36, characterized in that: The application includes use as a filter material when preparing silicon carbide single crystals.
Citation Information
Patent Citations
Titanium carbide porous ceramic preform, brake disc and preparation method
CN113755735A
S-band silicon-carbon-nitrogen ceramic wave-absorbing material and preparation method thereof
CN116409999A